Reconstructing the Formative Assessment of Teaching Modules for News and Advertisement Texts for Junior High School Students in the Merdeka Curriculum - Kumalasari, Riri; Kinanthi Aulina, Khanifa; Luriawati Naryatmojo, Deby; Wagiran, Wagiran (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study discusses the reconstruction of formative assessment in the teaching module for news and advertisement texts for junior high school students in the context of the Merdeka Curriculum. The aim of this study is to improve the effectiveness of formative assessment by analyzing the suitability between learning objectives, test items, and assessment rubrics. Using a qualitative descriptive approach, data were collected through an in-depth analysis of teaching modules from three schools, namely SMPN 7 Semarang, SMPN 30 Semarang, and SMPN 1 Margorejo. This study revealed that the previous formative assessment was less structured and only assessed basic understanding. The reconstruction was carried out by compiling questions based on critical thinking and a detailed assessment rubric. As a result, the assessment became more accurate, feedback was more meaningful, and student engagement increased. Practically, the results of this study can be a reference for teachers in designing formative assessments that are more effective and in line with learning outcomes, thus supporting the improvement of the quality of language learning in the classroom.